Narrativas, algoritmos e o controle tentativo no processo de gamificação: dos agenciamentos dos processos à materialização da experiência mental - Cortes, Dinis Ferreira (Universidade do Vale do Rio dos Sinos, 2022)
The present research seeks to understand the logics of media processes in the relationships between platforms, involved between algorithms and interaction, from the perspective of mediatization. The conceptual references on mediatization are: environment and ambience Among the authors works are (Gomes, 2017) mediatization as a mental experience and algorithms as logical means (Verón, 2014), with the concept of ambience; Behs and Ferreira (2019), Ferreira (2020) and circulation with the perspective of the materialization of mental experience (Fausto Neto (2020) and Rosa (2016). In interfaces, Syd Field (2001) with the idea of building characters and the conception of turning points in and the concept of gamification proposed by Garris, Ahlers, Driskell (2002) called Game Cycle. The interactors in movie-game works. As corpus we selected the game-movie Black Mirror – Bandersnatch and the movie-game The Dark Pictures Anthology – Man of Medan. By analogies, observations were also considered as analogical hypotheses with other movie-games such as Late Shift. Theoretical frameworks that discuss the algorithm and the space of semiosis, social imaginary, avatar and metaverse are tensioned. Our central questions proposed are: to research what are the relationships between logics of production and logics of recognition in the context in which the algorithmic means are means of the means, starting to manage the means of content and interaction (Ferreira, 2020); How is the agency between the algorithm and the interactor done, what are the possible paths and, consequently, what is at stake in this relationship? The objective is to understand the phenomena involved in the constitution of narratives from the assemblage of algorithms; to map the perception of the interactors in the face of the tentative control imposed by what the researcher calls devices of affection and allusions; in the context of gamification, to reflect on the functioning of the processes of materialization of the mental experience in a movie-game or game-film. As methodological contributions, we analyzed the production system and, through experimentation, we used a cartographic process – referenced in the to a Grounded Theory (Fragoso, Recuero and Amaral, 2013, p.84). The method is guided, being guided also by Peirce and the processes of abduction, deduction and induction (Peirce, 2005). In the course of the investigation, we look for clues as to how we can think about the paths taken and the semiosis agency and what can we understand from this new narrative format since they are tensioned by the uses, practices and tentative appropriations. The work contemplates the formulation of a previous analysis as a reference for the development of a theoretical foundation that seeks to understand the phenomena involved in the constitution of narratives from the agency of algorithms, the tentative control imposed by what the researcher calls devices of affections and allusions of how in gamification the processes of materialization of the mental experience work in a movie-game or game-film. Theoretical frameworks that discuss the algorithm and the space of semiosis, social imaginary, avatar and metaverse are tensioned. Experiments were carried out to collect data on how the semiosis process is carried out and how paths can be made within the interactive process of games.
Keywords: Midiatização; Narrativas midiáticas; Algoritmos; Gamificação; Materialização da experiência mental; Mediatization; Media narratives; Algorithms; Gamification; Materialization of mental experience; ACCNPQ::Ciências Sociais Aplicadas::Comunicação